Yicathins B and C and Analogues: Total Synthesis, Lipophilicity and Biological Activities. (1st April 2020) - Loureiro, Daniela R. P.; Magalhães, Álvaro F.; Soares, José X.; Pinto, Joana; Azevedo, Carlos M. G.; Vieira, Sara; Henriques, Ana; Ferreira, Helena; Neves, Nuno; Bousbaa, Hassan; Reis, Salette; Afonso, Carlos M. M.; et al.
Abstract: Natural products have always been an important source of new hits and leads in drug discovery, with the marine environment being regarded as a significant source of novel and exquisite bioactive compounds. Yicathins B and C are two marine‐derived xanthones that have shown antibacterial and antifungal activity. Herein, the total synthesis of these yicathins and six novel analogues is reported for the first time. As marine natural products tend to have very lipophilic scaffolds, the lipophilicity of yicathins and their analogues was evaluated in the classical octanol/water system and a biomimetic model‐based system. As the xanthonic nucleus is a "privileged structure", other biological activities were evaluated, namely antitumor and anti‐inflammatory activities. An interesting anti‐inflammatory activity was identified for yicathin analogues that paves the way for the design of dual activity (anti‐infective and anti‐inflammatory) marine‐inspired xanthone derivatives. Abstract : The total synthesis of two dual activity marine xanthones ‐ yicathins B and C ‐ and six additional analogues is reported. The lipophilicity of the synthetized compounds was evaluated by using biomimetic models. Their in vitro antitumor and anti‐inflammatory activities were also evaluated.